Etyka zawodowa w rachunkowości i Działania Stowarzyszenia Księgowych w Polsce w tym zakresie - Karmańska, Anna (Professional ethics in accounting activities in this scope undertaken by the accountants association in Poland, 2008)
The aim of this paper is to show the wide range of problems closely connected with professional ethics in accounting. The author shows the activities that The Accountants Association in Poland have been undertaking to make its members achieve the highest level of professional competences and follow ethical rules and standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 36-52